Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18052/www.scipress.com/ilcpa.54.47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Food Products for Pesticide Residue in Major Markets of Oyo State, Nigeria

Abstract: ABSTRACT.A study was carried out on the assessment of selected food produce for pesticide residue in Oyo State. With the aid of multi stage sampling technique, 8 selected markets were surveyed in the major constituencies of Oyo State which included Oje and Bodija Market in Ibadan, Arada and Sabo Markets in Ogbomoso, Ajegunle and Araromi Market in Oyo, Owode and Sango Markets in Igboho and Saki respectively in Oke-Ogun. Information on type of pesticide use, reason for choosing the pesticide, method of applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Phostoxin which is usually used as fumigant insecticides is the most predominantly used pesticides in the study area. This was in agreement with the reports from earlier researchers (Deji, 2012;Adesina et al, 2015), that Phostoxin was found to be used mostly in preserving foods. Combination of two pesticides will have fast and quick effects on the pest of the foodstuffs but with adverse effects on the health of man with a higher tendency of pesticides residues Adesina et al (2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Phostoxin which is usually used as fumigant insecticides is the most predominantly used pesticides in the study area. This was in agreement with the reports from earlier researchers (Deji, 2012;Adesina et al, 2015), that Phostoxin was found to be used mostly in preserving foods. Combination of two pesticides will have fast and quick effects on the pest of the foodstuffs but with adverse effects on the health of man with a higher tendency of pesticides residues Adesina et al (2015).…”
Section: Discussionsupporting
confidence: 94%
“…Majority of the respondents in the study area (56.67 %) stored foodstuff for less than a month before disposing it to the general public for consumption, this might result in food poisoning or contamination, and in agreement with the study by Adesina et al (2015). Adesina et al (2015) reported that storing of food crops for less than a month, might be because many do not understand the concept of withholding period which is the maximum length of time that must elapse. It is also a time a person must wait after application of pesticide on food crop before it is safe for consumption.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 76%
“…These two organochlorine pesticide residues classified as dangerous by the World Health Organization [38] could cause serious health and environmental risks. Moreover, the use of aluminum phosphide marketed as Phostoxin, which is a highly toxic pesticide banned in several countries [39], was registered by Adesina et al [40] as use by traders for yam chip protection. It is therefore important to sensitize farmers and traders to the use of chemical insecticides suitable for the protection of yam chips.…”
Section: Synthetic Insecticidesmentioning
confidence: 99%